Microcredit Interest Rates and Their Determinants, 2004-2011 - Rosenberg, Richard (CGAP, Washington, DC, 2014)
From the beginning of modern microcredit, its most controversial dimension has been the interest rates charged by micro lenders, often referred to as microfinance institutions (MFIs). These rates are higher, often much higher, than normal bank rates, mainly because it inevitably costs more to lend and collect a given amount through thousands of tiny loans than to lend and collect the same amount in a few large loans. Higher administrative costs have to be covered by higher interest rates. Many people worry that poor borrowers are being exploited by excessive interest rates, given that those borrowers have little bargaining power, and that an ever-larger proportion of microcredit is moving into for-profit organizations where higher interest rates could, as the story goes, mean higher returns for the shareholders. Section one looks at the level and trend of micro lenders' interest rates worldwide, and breaks them out among different types of institutions (peer groups). Section two examines the cost of funds that micro lenders borrow to fund their loan portfolio. Section three reports on loan losses, including, worrisome recent developments in two large markets. Section four presents trends in operating expenses, and touches on the closely related issue of loan size. Section five looks at micro lenders' profits, the most controversial component of microcredit interest rates. A reader without time to read the whole paper may wish to skip to section six, which provides a graphic overview of the movement of interest rates and their components over the period and a summary of the main findings. The annex describes our database and methodology, including the reasons for dropping four large microlenders6 from the analysis.